Enhanced Adaptive Neuro-Fuzzy Inference System Using Reptile Search Algorithm for Relating Swelling Potentiality Using Index Geotechnical Properties: A Case Study at El Sherouk City, Egypt; Mathematics; Vol. 9, iss. 24 - El-Shinawi А. А. Abdelaziz; Ali Ibrahim R. Rehab; Abualigah L. Laith; Zelenakova M. Martina; Mokhamed Elsaed (Mohamed Abd Elaziz) A. M. Akhmed Mokhamed (2021, 2021)
Title screen